A Tale of Two Trans Men: Transmasculine Identity and Trauma in Two Fairy-Tale Retellings - Jorgensen Jeana (Open Cultural Studies, 2021)
Transgender identities in fairy tale retellings are rare, but can reveal much about gender fluidity. Helen Oyeyemi’s novel Boy, Snow, Bird conflates transgender identities with mirrored falsehoods and fairy-tale spells, pathologizing a trauma victim who turns out to also become an abuser, while Gabriel Vidrine’s novella “A Pair of Raven Wings” depicts a queer transgender man with dignity, making it clear that the trauma he suffers is at the hands of bigots rather than being an invention of a sick mind or the cause of his transition. Pairing these fairy-tale retellings illuminates the topic of gender fluidity in fairy tales by demonstrating that gender is indeed fluid, but that representations of gender fluidity due to trauma are misguided at best and harmful at worst, while those representations that assert the dignity of transgender people, even as they face trauma at the hands of bigoted people, are another stellar example of the genre’s potential to represent people who are culturally marginalized, connecting identity to power in a classic magical fairy-tale move.